2019
DOI: 10.1186/s12970-019-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium bicarbonate ingestion during 6 weeks of HIIT on anaerobic performance of college students

Abstract: Background Past studies have found that sodium bicarbonate ingestion prior to exercise has a performance-enhancing effect on high-intensity exercise. The aim of this study was to investigate the effects of continuous sodium bicarbonate (NaHCO 3 ) supplementation on anaerobic performance during six weeks of high-intensity interval training (HIIT). Methods Twenty healthy college-age male participants were randomly assigned to either the HCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
4
22
1
2
Order By: Relevance
“…However, similar increases in cytochrome-c oxidase and βhydroxyacyl-CoA dehydrogenase (β-HAD) maximal activities were found in active but untrained men taking β-alanine or a placebo during six weeks of Sprint Interval Training (SIT) (three sessions per week) [55], suggesting differences in peripheral adaptations may not be seen when total work performed is the same. This is in contrast to some findings for sodium bicarbonate [33,34].…”
Section: Beta-alaninecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, similar increases in cytochrome-c oxidase and βhydroxyacyl-CoA dehydrogenase (β-HAD) maximal activities were found in active but untrained men taking β-alanine or a placebo during six weeks of Sprint Interval Training (SIT) (three sessions per week) [55], suggesting differences in peripheral adaptations may not be seen when total work performed is the same. This is in contrast to some findings for sodium bicarbonate [33,34].…”
Section: Beta-alaninecontrasting
confidence: 99%
“…Ingestion of sodium bicarbonate before each cycling interval training session (24 sessions over eight weeks) in recreationally-active women resulted in greater improvements in the lactate threshold (26 vs. 15%, d = 0.5) and time to fatigue (164 vs 123%, d = 1.9) compared with a placebo, even though training volume and intensity was matched between groups (Table 1) [33]. Six weeks of high-intensity interval training (HIIT) (18 sessions) by recreationally-active men consuming sodium bicarbonate or a placebo prior to each training session led to greater improvement in relative peak power (20.8 vs. 10.3%, d = 2.1) but no differences in relative mean power on a Wingate test [34], and similar improvements in time to fatigue, maximum power, and lactate threshold power, though only the bicarbonate group had significant increases in CS activity (22.3 vs. 12.6%) [35]. However, four weeks of sodium bicarbonate supplementation in highly-trained male rowers did not provide significant performance benefits compared with a placebo [36].…”
Section: Sodium Bicarbonatementioning
confidence: 99%
“…Edge et al [95] showed superior increases in lactate threshold (26% vs. 15%) and time to exhaustion (164% vs. 123%) after 8 weeks of 3x/week training (training progressed from six to 12 two minute intervals at 140-170% of the lactate threshold) in trained female participants who received sodium bicarbonate (0.2 mg/kg at 90 and 30 min) before training compared to placebo [95]. Additionally, Wang et al [96] demonstrated increases in relative peak power after 6 weeks of HIIT training three times per week in college-aged males [96].…”
Section: Sodium Bicarbonatementioning
confidence: 98%
“…The standards for exhaustion included: is the average oxygen consumption 30 s before reaching exhaustion 31 . W max was calculated as the power of the last completed stage plus the fraction of time spent in the nal non-completed stage multiplied by 30 W 32,33 . The rate of perceived exertion (RPE) and heart rate (HR) were measured during the test using the Borg scale (6-20) 34 and Polar V800 (Polar Electro Oy, Oulu, Finland).…”
Section: Graded Cycling Exercise Testmentioning
confidence: 99%